Dicey's song - Voigt, Cynthia (New York : Atheneum, 1982)
Now that the four abandoned Tillerman children are settled in with their grandmother, Dicey finds that their new beginnings require love, trust, humor, and courage.
Sequel to: Homecoming.
Keywords: Brothers and sisters -- Fiction; Families -- Fiction; Newbery Medal